PEMBELAJARAN BAHASA MAKASSAR BERBASIS TRANSFORMASI GENERATIF DI SEKOLAH DASAR - Mantasiah Rivai (Fakultas Sastra Universitas Negeri Malang, 2015)
This study aims at describing the implementation of Generative Transformation Grammar approach in the teaching of Makassar language in primary school. The steps in conducting this development research are by doing preparation,applying the model, conducting tests, evaluating and doing revision. The subjects in this study were students of SDN Pa’bangngiang Somba Opu sub-district at Gowa Regency which was randomly selected. Through the result of the tests, the students’ performance was measured which are collected and analyzed descriptively. The teaching and learning instructional materials developed are lesson plans, students’ book, and teachers guide based on TTG approach. The result of the study shows that the implementation of TTG approach in the teaching of Makassar language effectively increases the students’ knowledge and their performance to use the language